Letter (copy) : Julian Hickman Urrutia and Jesus Hickman Urrutia - Tewson, Vincent
027-0028-001 Secretary's. HVT/FC/EK/905. 15th April, 1940. Mr. G. W. Thomson, Association of Engineering and Shipbuilding Draughtsmen, 29, Arlington Court, Twickenham, MIDDLESEX. Dear Mr. Thomson, RE JULIAN HICKMAN URRUTIA AND JESUS HICKMAN URRUTIA. I am enclosing a copy of a letter which I have received from Senor J. I. de Lizaso of the Basque delegation in London. I am wondering if you could suggest any way of helping the two brothers referred to. They seem to be very experienced draughtsmen and your views would be greatly appreciated. Yours sincerely, Assistant Secretary. Copy of letter. 292/946/27/28